Trends in Underground Mining - Parra Paola O.; Marcos Quispe P.; Freddy Lobaton Z.; Adali Vela F.; Will Yucra C. (International Journal of Engineering and Management Research, 2021)
In this document, we will talk through information collected on all trends in mining in the underground environment as much as what happens in the world as or new machinery America provides the highest mining production in underground mining. We often discover opportunities for improvement in both productivity and costs. Of all these methods, braking is not only the most common, but also offers the largest share of overall production, nearly 50 percent. These underground mining methods are often determined by the deposits and the economics of mining and are therefore somewhat beyond the control of the operator(Trends in underground mining for gold and base metals | McKinsey, s. f.)